PENGARUH REFORMASI PELAYANAN PUBLIK E- GOVERNMENT TERHADAP REVITALISASI PENYELENGGARAAN BIROKRASIDI KANTOR IMIGRASI KOTA BOGOR - Yunita, Trizalia; Rahmawati, Rita; Rusliandy (Administratie: Jurnal Administrasi Publik, 2020)
This study is to explain the factors that influence the public through e-government, analyze the service objectives of respondents using information technology in providing public services. This research uses descriptive and verification research methods. Data collection techniques in this study were interviews and questionnaires. The data analysis technique used is the linear regression of correlation and coefficient of determination. The results of the study show that there are many factors that influence public services through e-government, namely commitment, quality of human resources, infrastructure, geographical conditions, and services. Information technology in public services already exists in the form of e-government. Respondents' responses to the implementation of public service reform were 4.19 in the good category, for revitalization 4.06 in the good category, and the highest at 4.48 including very good for indicators of complete payment systems such as websites and e-mail. Keywords: E-Government, Public Service Reform and Revitalization of Bureaucracy Implementation.